Extracellular vesicles released from stress‐induced prematurely senescent myoblasts impair endothelial function and proliferation. Issue 10 (26th August 2021) - Hettinger, Zachary R.; Kargl, Christopher K.; Shannahan, Jonathan H.; Kuang, Shihuan; Gavin, Timothy P.
Abstract : New Findings: What is the central question of this study? What is the impact of stress‐induced premature senescence on skeletal muscle myoblast‐derived extracellular vesicles (EVs) and myoblast–endothelial cell crosstalk? What is the main finding and its importance? Hydrogen peroxide treatment of human myoblasts induced stress‐induced premature senescence (SIPS) and increased the release of exosome‐sized EVs (30–150 nm in size) five‐fold compared to untreated controls. Treatment of SIPS myoblast‐derived EVs on endothelial cells increased senescence markers and decreased proliferation. Gene expression analysis of SIPS myoblast‐derived EVs revealed a four‐fold increase in senescence factor transforming growth factor‐β. These results highlight potential mechanisms by which senescence imparts deleterious effects on the cellular microenvironment. Abstract: Cellular senescence contributes to numerous diseases through the release of pro‐inflammatory factors as part of the senescence‐associated secretory phenotype (SASP). In skeletal muscle, resident muscle progenitor cells (satellite cells) express markers of senescence with advancing age and in response to various pathologies, which contributes to reduced regenerative capacities in vitro. Satellite cells regulate their microenvironment in part through the release of extracellular vesicles (EVs), but the effect of senescence on EV signaling is unknown. Primary human myoblasts were isolated following biopsies of the vastus lateralis from young healthy subjects. Hydrogen peroxide (H2 O2 ) treatment was used to achieve stress‐induced premature senescence (SIPS) of myoblasts. EVs secreted by myoblasts with and without H2 O2 treatment were isolated, analysed and used to treat human umbilical vein endothelial cells (HUVECs) to assess senescence and angiogenic impact. H2 O2 treatment of primary human myoblasts in vitro increased markers of senescence (β‐galactosidase and p21 Cip1 ), decreased proliferation and increased exosome‐like EV (30–150 nm) release approximately five‐fold. In HUVECs, EV treatment from H2 O2 ‐treated myoblasts increased markers of senescence (β‐galactosidase and transforming growth factor β), decreased proliferation and impaired HUVEC tube formation. Analysis of H2 O2 ‐treated myoblast‐derived EV mRNA revealed a nearly four‐fold increase in transforming growth factor β expression. Our novel results highlight the impact of SIPS on myoblast communication and identify a VasoMyo Crosstalk by which SIPS myoblast‐derived EVs impair endothelial cell function in vitro.